The effect of acutely administered MDMA on subjective and BOLD-fMRI responses to favourite and worst autobiographical memories. (April 2014) - Carhart-Harris, R. L.; Wall, M. B.; Erritzoe, D.; Kaelen, M.; Ferguson, B.; De Meer, I.; Tanner, M.; Bloomfield, M.; Williams, T. M.; Bolstridge, M.; Stewart, L.; Morgan, C. J.; et al.
Abstract 3, 4-methylenedioxymethamphetamine (MDMA) is a potent monoamine-releaser that is widely used as a recreational drug. Preliminary work has supported the potential of MDMA in psychotherapy for post-traumatic stress disorder (PTSD). The neurobiological mechanisms underlying its putative efficacy are, however, poorly understood. Psychotherapy for PTSD usually requires that patients revisit traumatic memories, and it has been argued that this is easier to do under MDMA. Functional magnetic resonance imaging (fMRI) was used to investigate the effect of MDMA on recollection of favourite and worst autobiographical memories (AMs). Nineteen participants (five females) with previous experience with MDMA performed a blocked AM recollection (AMR) paradigm after ingestion of 100 mg of MDMA-HCl or ascorbic acid (placebo) in a double-blind, repeated-measures design. Memory cues describing participants' AMs were read by them in the scanner. Favourite memories were rated as significantly more vivid, emotionally intense and positive after MDMA than placebo and worst memories were rated as less negative. Functional MRI data from 17 participants showed robust activations to AMs in regions known to be involved in AMR. There was also a significant effect of memory valence: hippocampal regions showed preferential activations to favourite memories and executive regions to worst memories. MDMA augmented activations to favourite memories in the bilateral fusiform gyrus and somatosensory cortex and attenuated activations to worst memories in the left anterior temporal cortex. These findings are consistent with a positive emotional-bias likely mediated by MDMA's pro-monoaminergic pharmacology.